Clinical research in Asia : opportunities and challenges - Sahoo, Umakanta; ScienceDirect eBooks (Cambridge : Woodhead Pub., 2012)
Asia is increasingly taking on a leading role in the fields of Good Clinical Practice (GCP) and ethics, two areas that are central to clinical research practices worldwide. Clinical research in Asia examines the evolution of these key sectors in the Asian countries where the greatest developments are taking place, offering valuable perspectives on a wide range of issues affecting clinical research. Following an introduction that provides an overview of the topic and its strengths and weaknesses, each chapter of the book is devoted to clinical research in a specific country, focusing on issues including the history and evolution of clinical research, clinical trials and regulatory aspects. The chapters also offer a perspective on future trends in clinical research in each country. The book concludes with a discussion of the importance of political, economic, socio-cultural, technological, legal and environmental factors (PESTLE analysis). Analysis from a leading and highly respected professional in the sectorAn overview of country-specific regulatory environmentsDiscussion of challenges and solutions for clinical research.
Clinical research in Asia: A brief overview -- Clinical research in Japan -- Clinical research in India -- Clinical research in China -- Clinical research in South Korea -- Clinical research in Taiwan -- Clinical research in Singapore -- Clinical research in Thailand -- Clinical research in Malaysia -- Clinical research in Hong Kong -- Clinical research in the Philippines, Indonesia and Vietnam -- Conclusions.
Print version record.
Elsevier
Keywords: Clinical trials -- Asia; Research -- Contracting out -- Asia; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Clinical trials; Research -- Contracting out; Asia; Electronic books